Expanded terminal sedation in end-of-life care - Gilbertson, Laura (Journal of medical ethics, 2023)
Despite advances in palliative care, some patients still suffer significantly at the end of life. Terminal Sedation (TS) refers to the use of sedatives in dying patients until the point of death. The following limits are commonly applied: (1) symptoms should be refractory, (2) sedatives should be administered proportionally to symptoms and (3) the patient should be imminently dying. The term ‘Expanded TS’ (ETS) can be used to describe the use of sedation at the end of life outside one or more of these limits. In this paper, we explore and defend ETS, focusing on jurisdictions where assisted dying is lawful. We argue that ETS is morally permissible: (1) in cases of non-refractory suffering where earlier treatments are likely to fail, (2) where gradual sedation is likely to be ineffective or where unconsciousness is a clinically desirable outcome, (3) where the patient meets all criteria for assisted dying or (4) where the patient has greater than 2 weeks to live, is suffering intolerably, and sedation is considered to be the next best treatment option for their suffering. While remaining two distinct practices, there is scope for some convergence between the criteria for assisted dying and the criteria for ETS. Dying patients who are currently ineligible for TS, or even assisted dying, should not be left to suffer. ETS provides one means to bridge this gap.